2013
DOI: 10.1371/journal.pone.0062053
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a New Breed of Wine Yeast: Interspecific Hybridisation between a Commercial Saccharomyces cerevisiae Wine Yeast and Saccharomyces mikatae

Abstract: Interspecific hybrids are commonplace in agriculture and horticulture; bread wheat and grapefruit are but two examples. The benefits derived from interspecific hybridisation include the potential of generating advantageous transgressive phenotypes. This paper describes the generation of a new breed of wine yeast by interspecific hybridisation between a commercial Saccharomyces cerevisiae wine yeast strain and Saccharomyces mikatae, a species hitherto not associated with industrial fermentation environs. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 42 publications
0
74
0
2
Order By: Relevance
“…the genomes of interspecific hybrids originating from the same parents can stabilize differently, resulting in different genomic configurations, as reported in previous studies targeting interspecific hybrids (30,32,44,45). Newly developed interspecific hybrids show a broad temperature tolerance range.…”
Section: Figmentioning
confidence: 52%
See 2 more Smart Citations
“…the genomes of interspecific hybrids originating from the same parents can stabilize differently, resulting in different genomic configurations, as reported in previous studies targeting interspecific hybrids (30,32,44,45). Newly developed interspecific hybrids show a broad temperature tolerance range.…”
Section: Figmentioning
confidence: 52%
“…Prior to phenotypic characterization, the genomes of the newly developed hybrids were therefore stabilized by growing interspecific hybrids for approximately 70 generations in industrial lager beer medium (see Materials and Methods for details). This number is shown to be sufficient to stabilize the genomes of newly formed interspecific yeast hybrids within the Saccharomyces genus (29)(30)(31)(32). Genetic stability was confirmed by genetic fingerprinting, and hybrids were considered stable when, after stabilization, both the interdelta and R3-RAPD band patterns were identical for the four biological replicates tested (see Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…First, selective breeding contains the risk of yielding so-called crippled strains, i.e., strains that show improvement for the selected trait but perform worse for other industrially important phenotypes that were not selected for. This was encountered, for example, in the study of Bellon et al (30), where three out of five developed hybrids showed inferior fermentation performance. Therefore, the fermentation kinetics of the newly developed hybrids was monitored during the ale fermentations.…”
Section: Discussionmentioning
confidence: 93%
“…However, it is becoming increasingly evident that wine fermentations performed at lower temperature ranges are readily dominated by naturally occurring interspecific hybrids, including those formed between S. cerevisiae and either S. uvarum (González et al 2006;Le Jeune et al 2007) or S. kudriavzevii (González et al 2006;Erny et al 2012). In addition to naturally occurring interspecific hybrids, hybrids of S. cerevisiae and either S. paradoxus, S. kudriavzevii, or S. mikatae have been artificially induced for commercialization purposes (Bellon et al 2011(Bellon et al , 2013. Like the situation observed for S. pastorianus, these hybrid strains are often not complete and contain varying amounts of each parental genome (Dunn et al 2012;Erny et al 2012).…”
Section: Wine Yeast Hybridsmentioning
confidence: 99%